Classification of ultrasound breast morphology among women of different age and ethnic groups in Klang Valley, Malaysia - Ibraheem, Shahad Abdulwahhab (2016)
The present study analyzed the normal types of breast morphology, breast echo structure using ultrasound evaluation while examining the difference in breast morphytes among Malaysian females according to age groups. This was carried out with the main aim of providing an indepth knowledge to professionals so as to enhance their efficiency in the interpretation of B-mode ultrasound images and to also provide the standard size of each breast tissue. Breast morphology results were recorded according to different factors which are age groups, race, socio-demographic factors, family information, gynecological information, family history of breast cancer, physial activity, anthropometric measurements and supplements usage among repondents in Golden Horses Health Sacntuary. An analytic cross-sectional study design was used to determine the morphology of normal breast among the respondents at the imaging department of Golden Horses Health Sanctuary, Sri-Kembangan located in Klang Valley, Selangor, Malaysia. Ultrasound breast images of the respondents were captured using Philips ultrasound iu22 with linear array probe L17-5 (5-17MHz) while using radial position with depth 3.5-4.0cm and again 86%-87% for the left and right breast. The use of proportionate probability sampling method was used for the selection of respondents for this study. A pretested self-administered questionnaires written in Malay Langauge was administered to the respondents in order to collect the data. The prevalence of premenopausal and postmenopausal age were 35.66 ± 8.20 and 57.43 ± 5.43 years respectively. The average age of the respondents in first menstrual phase was 12.01±0.64 years. Findings of the study showed that there was a significant association between ethnicity and ultrasound breast morpholgy. Findings of ultrasound images showed that Indians ethnic owned the highest mean score in all breast tissue in pre menopausal age group compared with Malay and Chinese ethnic, subcutaneous fat was 7.61 ± 7.05mm, glandular tissue in Indian ethnic respondents was 22.51 ± 8.79 mm for right upper outer. The mean of fat lobules in right lower outer for Indian ethnic and Malay respondents in pre-menopausal were 26.57 ± 12.05 and 27.10 ± 11.51 mm respectively, while in Chinese ethnic respondents were 15.84 ± 9.51mm. The average value of ethnic groups was approximately the same in the four quadrants of right and left breast in pre-menopausal and post-menopausal age group for support ligaments, pectorals fascia, pectorals muscle and duct. Approximately the left breast has the same values as right breast in each breast tissue. However, Chinese ethnic showed highest frequency of parenchyma pattern and dense breast as compared with results of mammography. There was also significant association between breast morphology and most socio-demographic factors tested in this study and BMI in most quadrants of both breast while no significant association between Cholesterol level, supplements (calcium and vitamines) and physical activity was observed. Finally, this study observed that the prevalence and wide range size of ultrasound breast tissue between premenopausal and postmenopausal women were varied among the three ethnic groups. The findings of this study also revealed that ultrasound can be a good first row image modality in breast imaging.